The Relationship Between Hepatitis B Surface Antibody Levels and the Levels of Serum Glutamic Pyruvic Transaminase, Serum Glutamic Oxaloacetic Transaminase, and Total Bilirubin - Ni Putu Ditya Prabandari Dewi; Heri Setiyo Bekti; I Nyoman Purna (MEDICA (International Medical Scientific Journal), 2024)
Hepatitis B virus is a disease that can impair other functions of the liver. This study aims to determine the relationship between Hepatitis B antibody levels and the levels of SGOT (Serum Glutamic Oxaloacetic Transaminase), SGPT (Serum Glutamic Pyruvic Transaminase), and bilirubin. A quantitative analytic study with a cross-sectional approach was conducted. Data collection involved primary data in the form of hepatitis B serum samples and secondary data including SGOT levels, SGPT levels, bilirubin levels, age, gender, and medical history. The results showed a significant and inverse relationship between Hepatitis B antibody levels and SGOT levels, with a Sig. (2-tailed) value of 0.029 (<0.05) and a negative correlation coefficient of -0.627. Similarly, there was a significant and inverse relationship between Hepatitis B antibody levels and SGPT levels, with a Sig. (2-tailed) value of 0.003 (<0.05) and a negative correlation coefficient of -0.616. However, there was no significant relationship between Hepatitis B antibody levels and bilirubin levels, as indicated by a Sig. (2-tailed) value of 0.809 (>0.05), although the correlation was positive (correlation coefficient = 0.078). In conclusion, Hepatitis B antibody levels show a significant negative correlation with SGOT and SGPT levels, while the correlation with bilirubin levels is positive but not statistically significant.